Empowering textile and fashion designers with e-textiles for creative expression - Zhang,M; Stewart,R; Bryan-Kinns,N (MDPI, 2024)
In the field of textile and fashion design, there is a growing desire to integrate interactive technologies into creative work. Traditional design education typically lacks support for material-oriented designers to develop electronic skills alongside their expertise in materials. There is a need to develop proper support for these designers to enter the world of electronic textiles (e-textiles). Our previous work introduced a material-centred e-textile learning approach through the development of a toolkit. This paper offers a glimpse into a design project made by our students, where digital functionality intertwines with physical design. It serves as a testament to the effectiveness of our approach in merging interactive technology concepts with material expertise, thereby aiding these designers in their creative endeavours.